Fuel properties and precipitate formation at low temperature in soy-, cottonseed-, and poultry fat-based biodiesel blends - Tang, Haiying; Salley, Steven O.; Simon Ng, K.Y. (Fuel (Guildford), 2008)
The formation of precipitates in biodiesel blends may have serious implications for diesel engine fuel delivery systems. Precipitates were observed in Soybean oil (SBO-), cottonseed oil (CSO-), and poultry fat (PF-) based biodiesel blends after storage at 4 °C. CSO- and PF-based biodiesel had a lower mass of precipitates observed than the SBO-based. Moreover, different rates of precipitate formation were observed for the B20 versus the B100. These suggested that the formation of precipitate during cold temperature storage was dependent on the feedstock and blend concentration. The solvency effects of biodiesel blends were more pronounced at low temperature than at room temperature leading to a higher amount of precipitates formed. Fourier transform infrared (FTIR) spectra, and gas chromatography-flame ionization detector (GC-FID) chromatograms indicated that steryl glucosides are the major cause of precipitate formation in SBO-based biodiesel; while for PF-based biodiesel, the precipitates are due to mono-glycerides. However, the precipitates from CSO-based biodiesel are due to both steryl glucosides and mono-glycerides.